Burnt Shadows: “Home”, “Cosmopolitanism” and “Hybridization” - Babar, Shazia (The Journal of Humanities & Social Sciences, 2023)
Multi-cultural societies, according to the cultural theorist Homi Bhabha, are in the process of developing hybrid identities that are in a state of flux. Shamsie’s Burnt Shadows reflects an individual who retains a strong link with the past but also develops in the future. For the protagonist displacement and loss is an on-going process yet is a living example of a person who can adjust in varied cultures. In contrast Raza the cosmopolitan, with a fluid identity has the capacity to form a new identity from diverse cultural sources. Bhabha’s concept of cultural identity provides the backdrop for the reader to reach an understanding of identity.